The Role of the Media in Combatting Terrorism and European Standards - Jovašević, Ana (Zbornik Instituta za kriminološka i sociološka istraživanja, 2013)
The first Conference of Ministers in charge of the media and new communication services in member states of the Council of Europe took place in Reykjavik (Iceland) at the end of May 2009. On that occasion, one political declaration and several resolutions MCM (2009) 011 were adopted. In this way, grounds were set for the new role of the media at the beginning of the third millennium. Standards set in this manner oblige all member states of the Council of Europe, including the Republic of Serbia. This concept of promoting awareness, comprehension, peace and tolerance, as well as preventing any kind of conflicts and achieving stable integration and cohesion in every society, was actually established in 2005 on the Third Summit of Heads of State and Government of Council of Europe Member States. These established goals were confirmed later in the same year in the Faro Declaration on the Council of Europe’s Strategy for Developing Intercultural Dialogue, adopted by Member States’ Ministers of Culture. Just like the traditional media, new providers of mass communication services that are similar to the media (electronic media, internet and other forms of computer and internet technologies) are supposed to support the improvement and the respect of fundamental human and social values. New modalities of creating the contents, the expression, the seeking and the dissemination of information in the sphere of mass communication may enhance but, at the same time, challenge fundamental rights and freedoms. Existing media standards that were developed for traditional forms of mass communication can also be applied to new services and to the providers of new media services (including their rights, duties and responsibilities).